2018
DOI: 10.4269/ajtmh.17-0697
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Preliminary Evaluation of a Novel Recombinant Protein for Serodiagnosis of Strongyloidiasis

Abstract: is a human parasite that can cause a long-term infection. In immunosuppressed patients, strongyloidiasis may be fatal when there is overwhelming autoinfection resulting in the migration of large numbers of larvae through many organs. Definitive diagnosis is still a challenge, and a combination of symptoms, microscopic identification, and serology test results are often used to arrive at a clinical decision. However, intermittent larval excretion, low parasite burden, and occult infections are challenges with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…When a combination of recombinant NIE and SsIR antigens was used in a LIPS assay, the sensitivity, specificity, positive predictive value, and negative predictive value were all 100%. Recently, Yunus et al, 2019 [41] used a combination of recombinant NIE and Ss1a [28] antigens to detect IgG4 antibody by lateral flow dipstick test and ELISA and found the sensitivity of both tests to be 91.3 and specificity to be 100%. In the present study, the diagnostic sensitivity, specificity, positive predictive value, and negative predictive value of the rSsIR-based IgG ICT kit for IgG antibody detection were 91.7%, 83.8%, 76.4%, and 94.6%, respectively, and those of the rSsIR-based IgG4 ICT kit for IgG4 antibody detection were 78.3%, 84.8%, 74.6%, and 87.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a combination of recombinant NIE and SsIR antigens was used in a LIPS assay, the sensitivity, specificity, positive predictive value, and negative predictive value were all 100%. Recently, Yunus et al, 2019 [41] used a combination of recombinant NIE and Ss1a [28] antigens to detect IgG4 antibody by lateral flow dipstick test and ELISA and found the sensitivity of both tests to be 91.3 and specificity to be 100%. In the present study, the diagnostic sensitivity, specificity, positive predictive value, and negative predictive value of the rSsIR-based IgG ICT kit for IgG antibody detection were 91.7%, 83.8%, 76.4%, and 94.6%, respectively, and those of the rSsIR-based IgG4 ICT kit for IgG4 antibody detection were 78.3%, 84.8%, 74.6%, and 87.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant antigen from S. stercoralis third-stage larvae called "NIE" [25] has been established as a highly sensitive and specific antigen for antibody detection in the serodiagnosis of human strongyloidiasis [26,27]. In addition, the recombinant antigens, S. stercoralis IgG immunoreactive antigen rSsIR [26] and rSs1a [28], also have potential use in the serodiagnosis of human strongyloidiasis. In this study, we used rSsIR (GenBank: AAB97359.1) as an alternative antigen for an immunochromatographic test (ICT) kit and compared the effectiveness of an rSsIR-based IgG ICT kit (for detecting levels of IgG antibody) with an rSsIR-based IgG4 ICT kit (for detecting levels of IgG4 antibody) in the diagnosis of human strongyloidiasis.…”
Section: Introductionmentioning
confidence: 99%
“…ELISA test has limitations of inability to identify between current and past infection and lower sensitivity in diagnosing strongyloidiasis in patients with hematologic malignancies and/ or infected with HTLV-1 [5]. To overcome these limitations, Strongyloidesspeci c recombinant antigens, such as NIE, SsIR, and rSs1a have been used in ELISA kits [5,29,30,31].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Recombinant NIE is an established antigen for the diagnosis of Strongyloides infection. It is a 31-kDa protein derived from S. stercoralis L3 cDNA library identified by Ravi et al, 15 whereas rSs1a antigen was identified by Arifin et al 16 from immunoscreening of an S. stercoralis cDNA library derived from a mixture of L3 and adult worms. Both the rNIE and rSs1a have shown good diagnostic sensitivity and specificity when tested with different assays using either IgG or IgG4 as the detector reagent.…”
mentioning
confidence: 99%
“…Both the rNIE and rSs1a have shown good diagnostic sensitivity and specificity when tested with different assays using either IgG or IgG4 as the detector reagent. 14,[16][17][18] In the present study, diagnostic sensitivity was determined using serum samples that had previously been shown to be positive for Strongyloides infection by at least two methods, that is, direct larvae detection via microscopy and/or real-time PCR, and indirect detection by IgG-ELISA (SciMedx Corporation, Denville, NJ). With regard to the direct method, five samples were positive by microscopy and real-time PCR, seven samples were positive by microscopy (real-time PCR not performed), one sample was positive by microscopy but negative by real-time PCR, and ten samples were positive by real-time PCR (microscopy not performed).…”
mentioning
confidence: 99%